2020
DOI: 10.1212/wnl.0000000000010727
|View full text |Cite
|
Sign up to set email alerts
|

Cortical microstructure in the amyotrophic lateral sclerosis–frontotemporal dementia continuum

Abstract: Objective:We aimed to characterize cortical macro- and micro-structure of behavioral and cognitive changes along the amyotrophic lateral sclerosis (ALS) – frontotemporal dementia (FTD) continuum.Methods:We prospectively recruited 88 participants with a three-Tesla MRI structural and diffusion-weighted imaging sequences: 31 ALS, 20 bvFTD, and 37 cognitively normal controls. ALS participants underwent a comprehensive cognitive and behavioral assessment and were dichotomized in ALS without cognitive or behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 42 publications
4
32
1
1
Order By: Relevance
“…Clinical observations are widely supported by extra-motor neuroimaging findings. Structural imaging consistently reveals frontotemporal gray and white matter degeneration (14,15,18,(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188). Gray matter atrophy has been described in the anterior cingulate, insula, operculum, inferior frontal gyrus, superior temporal gyrus, cerebellum, parietal, and occipital cortex (1,6,7,14,15,20,179,185,(187)(188)(189)(190)(191).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical observations are widely supported by extra-motor neuroimaging findings. Structural imaging consistently reveals frontotemporal gray and white matter degeneration (14,15,18,(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188). Gray matter atrophy has been described in the anterior cingulate, insula, operculum, inferior frontal gyrus, superior temporal gyrus, cerebellum, parietal, and occipital cortex (1,6,7,14,15,20,179,185,(187)(188)(189)(190)(191).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Structural imaging consistently reveals frontotemporal gray and white matter degeneration (14,15,18,(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188). Gray matter atrophy has been described in the anterior cingulate, insula, operculum, inferior frontal gyrus, superior temporal gyrus, cerebellum, parietal, and occipital cortex (1,6,7,14,15,20,179,185,(187)(188)(189)(190)(191). White matter degeneration has been detected in the body of the corpus callosum, inferior longitudinal fasciculus, uncinate fasciculus, cerebellum, inferior frontal, middle temporal, superior temporal, orbitofrontal, occipital, and parietal regions (1, 5-7, 11, 14, 15, 18, 20, 175-191).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Although, as expected, ALS-FTD patients have shown the most severe atrophy involving widespread frontotemporal cortical areas and subcortical regions (e.g., the caudate nucleus) [ 82 , 83 ], significant GM loss in extensive frontal, temporal, and—to a lesser degree—more posterior cortical brain regions has been observed also in patients with subtle cognitive and/or behavioral impairment [ 82 , 84 ]. Among studies which assessed specifically ALS-cbi patients compared with ALS-cn, greater thinning of inferior frontal, temporal, cingulate, and insular cortices was associated with worse performance in executive, language, verbal fluency, social cognition, and episodic memory task [ 84 , 85 ], in contrast with the focal cortical thinning observed in the dorsal motor cortex of ALS-cn patients [ 86 ]. Reduced volumes of the precuneus [ 87 ] and subcortical structures, including the thalamus and the amygdala [ 88 ], have also been shown in ALS-ci compared with ALS-cn.…”
Section: Neuroimaging As a Biomarker Of Cognitive/behavioral Impairmentmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) studies have also demonstrated distinctive microstructural abnormalities of the white matter (WM) in ALS with mild cognitive/behavioral impairment, in terms of diffusivity alterations within extra-motor (i.e., associative) tracts, including the uncinate, cingulum, superior longitudinal fasciculus, and fornix [ 83 , 86 ], correlating with the severity of cognitive and behavioral alterations [ 17 ]. These findings, as well as a recent network-based study correlating the structural disruption of frontal networks with executive dysfunction in ALS patients [ 90 ], support the notion of cognitive impairment in this condition as the result of a “disconnection syndrome” occurring when extra-motor brain WM tracts are pathologically involved.…”
Section: Neuroimaging As a Biomarker Of Cognitive/behavioral Impairmentmentioning
confidence: 99%
“…The GM cortical reconstruction process was performed using in-house surface-based approach developed to measure the microstructural changes in neurodegenerative disorders 12,13,35 . We used Freesurfer tools to calculate the midpoint of each individual's cortical surface in order to avoid contamination by adjacent WM and cerebrospinal uid 12,13 .…”
Section: Grey Matter Diffusion Processingmentioning
confidence: 99%